1978
DOI: 10.1007/bf00384829
|View full text |Cite
|
Sign up to set email alerts
|

In vivo development of Echinostoma malayanum Leiper, 1911 with notes on effects of population density, chemical composition and pathogenicity and in vitro excystment of the metacercaria (Trematoda: Echinostomatidae)

Abstract: In vivo development of Echinostoma malayanum Leiper, 1911 was studied in white rats and the developmental process was arbitrarily divided into four stages: organogeny, vitellogenesis, formation of Mehlis' gland complex and cirrus sac, and oviposition. The percentage of development was 86-94. Population density affected the prepatent period of flukes and the normal prepatent period of 13-16 days was altered to 18-23 days in infection with 500-800 flukes. The majority of flukes in heavy infection were undersized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…RANKIN (1937) noted the relationship between number and size of trematodes within a host and suggested that crowding may be the factor involved. Other reports on crowding with intestinal trematodes include those by WILLEY (1941), FRIED & NELSON (1978), MOHANDAS & NADAKAL (1978), FRIED & FREEBORNE (1984) and FRANCO et al (1988). MOHANDAS & NADAKAL (1978) have shown retarded growth of Echinostoma malayanum at high parasite densities.…”
Section: Introductionmentioning
confidence: 96%
“…RANKIN (1937) noted the relationship between number and size of trematodes within a host and suggested that crowding may be the factor involved. Other reports on crowding with intestinal trematodes include those by WILLEY (1941), FRIED & NELSON (1978), MOHANDAS & NADAKAL (1978), FRIED & FREEBORNE (1984) and FRANCO et al (1988). MOHANDAS & NADAKAL (1978) have shown retarded growth of Echinostoma malayanum at high parasite densities.…”
Section: Introductionmentioning
confidence: 96%
“…Rankin (1937) noted the relationship between number and size of trematodes within a host and suggested that crowding may be the factor involved. Mohandas and Nadakal (1978) have shown retarded growth of Echinostoma malayanum at high worm densities. Mohandas and Nadakal (1978) have shown retarded growth of Echinostoma malayanum at high worm densities.…”
Section: Growthmentioning
confidence: 97%
“…Echinostoma malayanum causes mucosal destruction, edema of the lamina propria and hyperplasia of the epithelial cells in experimental rats (Mohandas and Nadakal, 1978). The backwardly-pointed collar spines most likely help the worm to secure itself in the mucosa.…”
Section: Pathogenesis and Host Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Trematodes mature and mate with their hermaphroditic conspecifics (although schistomes have separate sexes) and pass eggs (often with the host's feces) out of the host. If resources become limited in the host due to competition with other parasites, growth and egg production can suffer as can be seen in experimentally induced, highintensity infections with echinostomes (Mohandas and Nadakal, 1978).…”
Section: Adultsmentioning
confidence: 99%